2010
DOI: 10.1364/oe.18.003219
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid organic semiconductor/silicon photodiode for efficient ultraviolet photodetection

Abstract: A method employing conjugated polymer thin film blends is shown to provide a simple and convenient way of greatly enhancing the ultraviolet response of silicon photodetectors. Hybrid organic semiconductor/silicon photodetectors are demonstrated using fluorene copolymers and give a quantum efficiency of 60% at 200 nm. The quantum efficiency is greater than 34% over the entire 200-620 nm range. These devices show promise for use in high sensitivity, low cost UV-visible photodetection and imaging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…[4][5][6][7][8][9][10] A possible convenient means of circumventing the intrinsic limitations of organic photocapacitors is to create a hybrid photosensitive device by coating a silicon substrate with a suitable organic fi lm (such as a conjugated polymer) serving as an 'enhancement layer' for broadband UV-visible detection. [ 11,12 ] To fulfi ll this scope, the organic layer should exhibit a broadband spectral response, absorbing light at high energies where the silicon photo-response is poor, and should emit at longer wavelengths. [ 12 ] Improved photo-effi ciency would thus results from both a higher UV absorption coeffi cient and a substantial emission at longer wavelengths of the organic polymer, providing the silicon with photons enhancing the opto-electrical response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10] A possible convenient means of circumventing the intrinsic limitations of organic photocapacitors is to create a hybrid photosensitive device by coating a silicon substrate with a suitable organic fi lm (such as a conjugated polymer) serving as an 'enhancement layer' for broadband UV-visible detection. [ 11,12 ] To fulfi ll this scope, the organic layer should exhibit a broadband spectral response, absorbing light at high energies where the silicon photo-response is poor, and should emit at longer wavelengths. [ 12 ] Improved photo-effi ciency would thus results from both a higher UV absorption coeffi cient and a substantial emission at longer wavelengths of the organic polymer, providing the silicon with photons enhancing the opto-electrical response.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11,12 ] To fulfi ll this scope, the organic layer should exhibit a broadband spectral response, absorbing light at high energies where the silicon photo-response is poor, and should emit at longer wavelengths. [ 12 ] Improved photo-effi ciency would thus results from both a higher UV absorption coeffi cient and a substantial emission at longer wavelengths of the organic polymer, providing the silicon with photons enhancing the opto-electrical response.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] When using bulk heterojunction (BHJ) structure, one seeks an organic electron donor/acceptor blend system to increase the photonto-charge conversion rate and resultant light sensitivity. [10,19,20] However, for OPTs containing electron donor/acceptor active layers, ambipolar behaviors are often observed. [10,19,20] However, for OPTs containing electron donor/acceptor active layers, ambipolar behaviors are often observed.…”
mentioning
confidence: 99%
“…[12,18] This concept has been successfully applied to organic photodiodes with a sandwich device geometry. [10,19,20] However, for OPTs containing electron donor/acceptor active layers, ambipolar behaviors are often observed. As a result, the off-state current of OPTs can be lifted, which reduces the detectivity.…”
mentioning
confidence: 99%
“…In [11], TiO2 nano-crystalline film was prepared on SrTiO3 (001) substrate to form an n-n heterojunction active layer and final device shows a good responsivity in UV region. In another work [12] by employing conjugated polymer thin film blends, authors showed improving the ultraviolet response of silicon photodetectors for UV spectra. However these methods are not applicable in standard BiCMOS process.…”
Section: Introductionmentioning
confidence: 99%